Bad News, Bad Moves? How Emotion Regulation and Doomscrolling Shape Aggression - Indri Oktavia Rospita; Cleoputri Al Yusainy; Lusy Asa Akhrani (Universitas Ahmad Dahlan, 2026)
Cyber aggression in the context of social media has been widely studied. However, research explicitly examining the spillover of aggression from social media into real world behavior through news exposure, particularly in the form of initial unprovoked aggression, remains limited. Doomscrolling is assumed to increase initial unprovoked aggression, whereas emotion regulation is expected to attenuate its intensity. This study aimed to examine the moderating roles of emotion regulation and doomscrolling in the effect of news type on initial unprovoked aggression. A mixed experimental design with a quantitative approach was employed, involving 157 participants. Doomscrolling was measured using a self-report, whereas initial unprovoked aggression was assessed using the Competitive Reaction Time Task (CRTT). Data were analyzed using a linear mixed-effects model (LMM) in RStudio. The results indicated that news type did not have a significant effect on initial unprovoked aggression (B = 0.16, SE = 0.20, p = .429, 95% CI [−0.22, 0.60]). The three-way interaction among news type, emotion regulation strategy, and doomscrolling was also not significant, F(3, 306) = 1.65, p = .179.